Substantiation of methodological approaches in comparative educational studies. (Journal of Educational Sciences, 2016)
Given article discusses questions on methodological knowledge in comparative and pedagogical research. Questions on developmentof comparative pedagogy in contemporary context are brought up. Methodological principles and approaches of comparative and pedagogical research, in particular culturological, paradigmatic and systematic approaches are analyzed.
Keywords: comparative pedagogy; methodology of comparative pedagogics; methodological approaches of comparative educational research